Introduction to Indonesian culture for Thai students traditional dance training in as an effort - Trisakti, Trisakti; Yanuartuti, Setyo; Anggoro, Raden Roro Maha Kalyana Mitta (Universitas Ahmad Dahlan, 2024)
Traditional dance training activities for Thai students specifically aim to introduce Indonesian arts and culture on the international stage. This activity is motivated by the important role of relations between universities and society, especially people abroad. PKM which uses traditional dance as an object of training material has an important role as an effort to preserve traditional or local culture, respect traditional values, and develop local cultural potential, especially in traditional arts. The dance training which was attended by 12 (twelve) universities in Thailand with 166 training participants was held at the Bangkok Indonesian School Sports Building in Thailand. The aim of traditional dance training is to introduce Indonesian culture to Thai students. Traditional dance training methods use demonstration and practice methods.